2008
DOI: 10.3174/ajnr.a1169
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Changes Contribute to Corpus Callosum Atrophy in the Elderly: The LADIS Study

Abstract: on behalf of the LADIS study group BACKGROUND AND PURPOSE: The corpus callosum (CC) is the most important structure involved in the transmission of interhemispheric information. The aim of this study was to investigate the potential correlation between regional age-related white matter changes (ARWMC) and atrophy of CC in elderly subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 34 publications
(51 reference statements)
4
46
0
Order By: Relevance
“…This is consistent with the hypothesis that leukoaraiosis results in loss of white matter tract organization, 5 damage to intra-and interhemispheric white matter pathways with reduced functional network integrity, [6][7][8][9] and overall reduced ability to compensate for deficits produced by an acute ischemic stroke. 7 Nevertheless, although plausible, this hypothesis will require confirmation in additional studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is consistent with the hypothesis that leukoaraiosis results in loss of white matter tract organization, 5 damage to intra-and interhemispheric white matter pathways with reduced functional network integrity, [6][7][8][9] and overall reduced ability to compensate for deficits produced by an acute ischemic stroke. 7 Nevertheless, although plausible, this hypothesis will require confirmation in additional studies.…”
Section: Discussionsupporting
confidence: 78%
“…[2][3][4] In addition, leukoaraiosis-related loss of white matter tract organization with damage to intra-and interhemispheric white matter pathways could result in reduced functional network integrity. [5][6][7][8][9] This may impair brain plasticity and compensatory mechanisms for acute deficits such that even small strokes could result in relatively large functional deficits. 10 Hence, it is conceivable that the association between infarct volume and NIHSS is affected by the degree of pre-exisiting leukoaraiosis burden.…”
mentioning
confidence: 99%
“…36 In our study, 8 patients had atrophy of the corpus callosum, which is also reported in MS and dementia, a finding only partially explained by Wallerian degeneration. 37,38 There was U-fiber preservation in 93% of the patients with HDLS.…”
Section: Resultssupporting
confidence: 53%
“…The same template has been used in previous publications of the LADIS Study. 22,23 Reliability analysis revealed Ͼ0.90 (weighted Cohen ) intrarater agreement for both cortical and subcortical atrophy. Inter-rater agreement was 0.70 for cortical and 0.83 for subcortical atrophy.…”
mentioning
confidence: 99%
“…Inter-rater agreement was 0.70 for cortical and 0.83 for subcortical atrophy. 22,23 MTA was rated also by a single rater on the T1-weighted images resliced in the coronal plane according to the Scheltens scale ranging from 0 to 4 on the left and right hemispheres. 24 The average of these 2 scores was used in the present study.…”
mentioning
confidence: 99%